Microcluster-Based Incremental Ensemble Learning for Noisy, Nonstationary Data Streams - Sanmin Liu; Shan Xue; Fanzhen Liu; Jieren Cheng; Xiulai Li; Chao Kong; Jia Wu (Complexity)
Data stream classification becomes a promising prediction work with relevance to many practical environments. However, under the environment of concept drift and noise, the research of data stream classification faces lots of challenges. Hence, a new incremental ensemble model is presented for classifying nonstationary data streams with noise. Our approach integrates three strategies: incremental learning to monitor and adapt to concept drift; ensemble learning to improve model stability; and a microclustering procedure that distinguishes drift from noise and predicts the labels of incoming instances via majority vote. Experiments with two synthetic datasets designed to test for both gradual and abrupt drift show that our method provides more accurate classification in nonstationary data streams with noise than the two popular baselines.